Proud to be Croat - national identity and sports in the advertising world - Bartoluci, Sunčica (Array, 2011)
This paper analysed Croatian TV commercials in order to determine the way in which advertising utilizes national identity. The corpus consisted of 50 television ads placed either in a sports setting, employing sports imagery or including a celebrity athlete (Hilliard and Hendley, 2005). The analysis also included verbal and non-verbal expressions of national identity. The results show that dominant sports are soccer and handball in which national team is successful ; dominant product is beer ; sport setting is not unavoidable and it is often supplemented by sport supporters’ gatherings in various situations. The celebrities are most often national selectors or players. National identity is expressed verbally through slogans or songs which often exceed the limits of particular commercial and become national supporting songs. It is interesting to notice that except for the usual symbols of national identity (white and red checkered patterns, etc.) commercials often include Croatian natural beauty or cultural heritage.